Effect of Al2O3 Nanoparticles and Cylindrical Pins on Natural Convection Heat Transfer in a C-Shaped Enclosure - Arafat, M. Y.; Faisal, F. (Journal of Scientific Research, 2020)
A numerical study has been conducted to investigate the transport mechanism of natural convection in a C-shaped enclosure filled with water-Al2O3 nanofluid for various pertinent parameters. The effects of the volume fraction of the Al2O3 nanoparticles, Rayleigh number, and radius of inserted cylindrical pins on the temperature, velocity, heat flux profiles and average Nusselt number have been investigated. General correlations for the effective thermal conductivity and viscosity of nanofluids are used for this analysis. The governing mass, momentum and energy equations are solved numerically with the finite volume method using the SIMPLER algorithm. The results show that addition of nanoparticle improves the heat transfer performance. Insertion of cylindrical pins of lower radius increases the average Nusselt number irrespective of Rayleigh number. But anomaly has been observed while pins of higher radius are inserted due to enormous disturbance in the fluid.